2014
DOI: 10.1186/1471-2180-14-65
|View full text |Cite
|
Sign up to set email alerts
|

The antibacterial effect of nitric oxide against ESBL-producing uropathogenic E. coli is improved by combination with miconazole and polymyxin B nonapeptide

Abstract: BackgroundNitric oxide (NO) is produced as part of the host immune response to bacterial infections, including urinary tract infections. The enzyme flavohemoglobin, coded by the hmp gene, is involved in protecting bacterial cells from the toxic effects of NO and represents a potentially interesting target for development of novel treatment concepts against resistant uropathogenic bacteria. The aim of the present study was to investigate if the in vitro antibacterial effects of NO can be enhanced by pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…It has already been shown that NO can have an antimicrobial effect against multidrug-resistant uropathogenic E. coli . [44] In addition, a manganese nitrosyl, entrapped in the mesoporous material MCM-41 has been discovered to strongly inhibit the growth of drug-resistant A. baumannii . [45] Nevertheless, most of these studies to date have focused on the bactericidal properties of NO on planktonic cells.…”
Section: Resultsmentioning
confidence: 99%
“…It has already been shown that NO can have an antimicrobial effect against multidrug-resistant uropathogenic E. coli . [44] In addition, a manganese nitrosyl, entrapped in the mesoporous material MCM-41 has been discovered to strongly inhibit the growth of drug-resistant A. baumannii . [45] Nevertheless, most of these studies to date have focused on the bactericidal properties of NO on planktonic cells.…”
Section: Resultsmentioning
confidence: 99%
“…5,25 More recent data correlated the antibacterial activity with the inhibition of bacterial flavohaemoglobins. 26,27 Especially in inflammatory skin disease, such as atopic dermatitis, seborrhoeic dermatitis and psoriasis, microbes are believed to trigger, exacerbate or sustain the pathological processes. 3,4,6 Azoles with their combined antifungal and antibacterial effects against staphylococci, streptococci, dermatophytes and yeasts can be of great use in dermatology where infections are often mixed.…”
Section: Discussionmentioning
confidence: 99%
“…An extensive literature exists on the NO detoxification mechanisms of E. coli and is dominated by articles on the flavohemoglobin Hmp, reflecting the detoxification of NO to nitrate as an important process during infection. Indeed, the UPEC strain J96 has previously been shown to out-compete an isogenic hmp mutant in bladder and kidney colonisation in the mouse UTI model 14 , and pharmacological modulation of Hmp activity has recently been shown to elevate NO sensitivity in multidrug-resistant UPEC strains 34 . It is therefore reasonable to assume that Hmp provides considerable protection against nitrosative stress in vivo .…”
Section: Discussionmentioning
confidence: 99%